Flexural strength interlocking block beam laterite soil - Mohd Safuan, Ismail (2013)
Load bearing interlocking block (LBIB) is one of the methods in Industrialized Building System (IBS) as classified by the Construction Industry Development Board Malaysia (CIDB), Using the LBIB in the construction of houses is fast and does not require formwork. The channel blocks act as permanent formwork constructed as beams where lintels are placed above window and door openings. The aim of this research is to determine the flexural strength of lintels constructed using the interlocking channel blocks. Two types of channel blocks were used and two types of arrangements for block types and reinforcements were constructed. Four point bending test were carried out for the two beams of length 1800mm span. The experimental results were compared to theoretical calculations from basic mechanics of materials for composite beams and a formula derived by (Pongburanakit and Aramraks,2006). Results shows that the arrangement of two layers of channel blocks gives stronger flexural strength compared to that of the face to face channel blocks.